Perceived supervisor support as a relevant factor for subordinates' job satisfaction - model verification - Marcin Wnuk (Nofer Institute of Occupational Medicine, 2019)
Background Perceived supervisor support has a significant impact on employee job satisfaction. The aim of the study was to verify both direct and indirect mechanisms of perceived supervisor support (PSS) positively influencing job satisfaction, and to verify the moderating role of PSS in the relationships between stress and work-life balance, organizational loyalty, as well as gratitude towards the organization and job satisfaction. Material and Methods Four hundred and fifty-five employees from 1 organization were the subjects of the conducted research. The following measures were used: Perceived Supervisor Support Scale , Gratitude Towards the Organization Scale , Loyalty Towards the Organization Scale , Perceived Stress at Work Questionnaire , Satisfaction with Work-Life Balance Scale and 1-item measure regarding job satisfaction. Results Gratitude towards the organization, work-life balance and stress partially mediated between PSS and job satisfaction. Stress influenced job satisfaction both directly and indirectly (through gratitude towards the organization and work-life balance). Additionally, PSS moderated the relationships between stress and gratitude towards the organization, organizational loyalty, work-life balance, as well as job satisfaction. Conclusions The important role of leader-member exchange for employee job satisfaction was confirmed. Both direct and indirect mechanisms responsible for the influence of PSS on job satisfaction were recognized. Additionally, the moderating role of PSS for the relationships between stress and organizational loyalty, gratitude towards the organization, work-life balance, as well as job satisfaction was confirmed. Med Pr. 2019; 70(4):475-86